Advancements in the investigation of gut microbiota-based strategies for stroke prevention and treatment - Wang, Min; Liu, Yan; Zhong, Li; Wu, Fang; Wang, Jinjin (Frontiers in Immunology, 2025)
Stroke represents a predominant cause of mortality and disability on a global scale, impacting millions annually and exerting a considerable strain on healthcare systems. The incidence of stroke exhibits regional variability, with ischemic stroke accounting for the majority of occurrences. Post-stroke complications, such as cognitive impairment, motor dysfunction, and recurrent stroke, profoundly affect patients’ quality of life. Recent advancements have elucidated the microbiota-gut-brain axis (MGBA), underscoring the complex interplay between gut health and brain function. Dysbiosis, characterized by an imbalance in gut microbiota, is significantly linked to an elevated risk of stroke and unfavorable outcomes. The MGBA plays a crucial role in modulating immune function, neurotransmitter levels, and metabolic byproducts, which may intensify neuroinflammation and impair cerebral health. This review elucidates the role of MGBA in stroke pathophysiology and explores potential gut-targeted therapeutic strategies to reduce stroke risk and promote recovery, including probiotics, prebiotics, pharmacological interventions, and dietary modifications. However, the current prevention and treatment strategies based on intestinal flora still face many problems, such as the large difference of individual intestinal flora, the stability of efficacy, and the long-term safety need to be considered. Further research needs to be strengthened to promote its better application in clinical practice.